Reducing ageism combining ageing education with clinical practice: A prospective cohort study in health sciences students - Batirtze San‐Martín‐Gamboa; Idoia Zarrazquin; Ainhoa Fernandez‐Atutxa; Silvia Cepeda‐Miguel; Borja Doncel‐García; Idoia Imaz‐Aramburu; Amaia Irazusta; Ana B. Fraile‐Bermúdez (Wiley, 2023)
Abstract Aim To analyse the impact of an intervention combining ageing education with clinical practice in nursing homes on a nursing cohort's negative stereotypes and prejudices towards ageing. Design A prospective cohort study was conducted in September 2019-October 2020 in a population of health sciences students (n = 222). Methods Questionnaire of Negative Stereotypes towards Aging (CENVE) and Aging Semantic Differential (DSE) were used to examine negative stereotypes and prejudices towards ageing in the nursing cohort exposed to the ageing education and practice intervention compared to a medical cohort that received no intervention. Group‐by‐time interaction, controlled by sex and age, for the effect of the intervention on CENVE and DSE scores was determined by mixed‐design ANOVA. Results The nursing cohort significantly reduced negative stereotypes and prejudices towards ageing when compared to the medical cohort in total (F = 26.926; p < 0.001), health factor (F = 16.812; p < 0.001), motivational and social factor (F = 11.266; p = 0.001), and character and personality factor (F = 19.202; p < 0.001) scores of CENVE scale and in DSE (F = 7.826; p = 0.006).